Prevalence and Population Genetics Analysis of Enterocytozoon bieneusi in Dairy Cattle in China - Wang, Hai-Yan; Qi, Meng; Sun, Ming-Fei; Li, Dong-Fang; Wang, Rong-Jun; Zhang, Su-Mei; Zhao, Jin-Feng; Li, Jun-Qiang; Cui, Zhao-Hui; Chen, Yuan-Cai; Jian, Fu-Chun; Xiang, Rui-Ping; et al. (Frontiers in Microbiology, 2019)
Enterocytozoon bieneusi, an obligate intracellular pathogen, can infect various hosts. In this study, 3527 dairy cattle fecal specimens were collected from different geographic locations in China (including 673 from Shandong province, 1440 from Guangdong province and 1414 from Gansu province) and examined for the presence of E. bieneusi using polymerase chain reactions targeting the ribosomal internal transcribed spacer (ITS). The dominant genotypes identified were further subtyped by multilocus sequence typing. The overall prevalence of E. bieneusi was 14.2% (501/3527), with a significant difference in prevalence among the different geographical locations (P < 0.001). Our logistic regression analysis showed that all four variables (farming model, location, age and clinical manifestations) had strong effects on the risk of contracting E. bieneusi. Sequence analysis revealed 11 genotypes: eight known genotypes (J, I, BEB4, BEB10, D, EbpC, CM19 and CM21) and three novel genotypes (named here as CGC1, CGC2 and CGC3). Genotypes J and I, the commonest, were found on all farms across the three provinces. Our linkage disequilibrium analysis showed a clonal population structure in the E. bieneusi dairy cattle population but the ITS genotypes had different population structures. Phylogenetic and haplotype network analysis showed the absence of geographical segregation in the E. bieneusi dairy cattle populations. Instead, they revealed the presence of host adaptation to the E. bieneusi populations in various animals. Our findings augment the current understanding of E. bieneusi transmission dynamics.